2005
DOI: 10.1185/030079905x30699
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, investigator-masked clinical trial comparing the efficacy and safety of gatifloxacin 0.3% administered BID versus QID for the treatment of acute bacterial conjunctivitis

Abstract: In this study, gatifloxacin 0.3% administered BID was as effective and as safe as gatifloxacin 0.3% administered QID for 5 days for the treatment of bacterial conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…22 Fluoroquinolones are concentrationdependent antibacterial agents 23 ; therefore, increasing the concentration of gatifloxacin may improve efficacy. In addition, enhancing the antibacterial activity of gatifloxacin 0.3% also may help prevent selection of resistant mutants.…”
Section: Introductionmentioning
confidence: 99%
“…22 Fluoroquinolones are concentrationdependent antibacterial agents 23 ; therefore, increasing the concentration of gatifloxacin may improve efficacy. In addition, enhancing the antibacterial activity of gatifloxacin 0.3% also may help prevent selection of resistant mutants.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Studies have shown that topical gatifloxacin solution may be effective in prevention of infectious conditions such as conjunctivitis, keratitis, and postcataract endophthalmitis. 15,16 Owing to the benefits offered by gatifloxacin, various manufacturers have introduced gatifloxacin eyedrops (0.3% wt/vol). Fluoroquinolones have pHdependent solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Two cases out of twelve who were administered Tobramycin and one out of six administered Ofloxacin were using the drug twice a day instead of the standard regimen of six hourly administration 13 . One person was incorrectly administered Gatifloxacin three times a day against the standard regimen of six hourly dosing 14 .…”
Section: Discussionmentioning
confidence: 99%